HASIL BELAJAR TARIKH MELALUI METODE JIGSAW DAN METODE MIND MAP DI SMP MUHAMMADIYAH 13 BOYOLALI - Badrus Zaman (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2020)
This study aims to improve the learning outcomes of the Date by using the jigsaw method and the mind map method of class VIII at SMP Muhammadiyah 13 Wonosegoro, Boyolali in the academic year 2019/2020. This research is a Classroom Action Research with stages of planning, implementation, observation, and reflection. The data collection methods used include observation, tests, and documentation. The analysis used by researchers is to compare the achievement of values ​​with the Minimum completeness Criteria (KKM) and is characterized by increasing classical completeness criteria in each cycle. This can be proven by an increase in each cycle that has been carried out. In the pre cycle the percentage of completeness was only 33.3% or 5 students and 10 other students or 66.7% had not been completed. In Cycle I there was an increase in learning outcomes to 66.7% or 10 students and 33.3% or 5 unfinished students. in the second cycle there was an increase to 13 students who were completed or 86.7% and 2 students who were not yet finished or 13.3%.